Determinasi Kepemimpinan Transformasional Kepala Sekolah, Komunikasi Interpersonal, dan Motivasi Kerja Terhadap Komitmen Organisasi Guru SMA Negeri 3 Kuta Selatan - Ni Kadek Indah Permata; Kadek Rihendra Dantes; Basilius Redan Werang (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to 1) describe the determination of transformational leadership towards the organizational commitment of SMA Negeri 3 Kuta Selatan teachers, 2) describe the determination of interpersonal communication towards the commitment of SMA Negeri 3 South Kuta teacher organization, 3) describe the determination of work motivation towards the commitment of SMA Negeri 3 South Kuta teacher organization, 5) describe the amount of simultaneous determination of transformational leadership, interpersonal communication, and work motivation towards the commitment of the teacher organization of SMA Negeri 3 South Kuta. This study was an "ex-post facto" study with a large sample of 30 people. Data was collected by questionnaires and documents. Data analysis was performed by simple regression, multiple regression, and partial correlation techniques. The results showed that: (1) there was a significant determination between transformational leadership and organizational commitment of SMA Negeri 3 Kuta Selatan, with a correlation coefficient of 0.977 and an effective contribution of 18.72%. (2) there is a significant determination between interpersonal communication and organizational commitment of SMA Negeri 3 Kuta Selatan, with a correlation coefficient of 0.962 and an effective contribution of 7.6%. (3) there is a significant determination between work motivation and organizational commitment of SMA Negeri 3 Kuta Selatan, with a correlation coefficient of 0.959 and an effective contribution of 18.22%. (4) Together, there is a significant determination between transformational leadership, interpersonal communication and work motivation towards the organizational commitment of SMA Negeri 3 Kuta Selatan, with a double correlation coefficient of 0.980 and a determination of 96.0% to organizational commitment at SMA Negeri 3 Kuta Selatan.